Called to the missional frontline in a turbulent world: The role of theological education - Daniel N. Andrew (African Journal of Pentecostal Studies)
Background: The Apostolic Faith Mission International (AFMI) conference had as its theme called to the missional frontline in a turbulent world, but the topic of theological education never made it to the main agenda. The article engages with theological education in the context of a Western hegemonic epistemology that dominates its provision in the Global South and in the African context.